The electro-oculogram in central retinal vein occlusion. Issue 9 (September 1992) - Papakostopoulos, D; Bloom, P A; Grey, R H; Dean Hart, J C
Abstract : As part of a prospective masked study, the electro-oculogram (EOG) was recorded from 28 patients within 48 days of developing central retinal vein occlusion (CRVO). The EOG light peak/dark trough ratio (Lp/Dt) x 100 was significantly lower in the affected than in the unaffected eyes of patients (p < 0.001), and abnormally low in absolute terms in 20 patients (71%). All unaffected fellow eyes had a normal EOG ratio. The mean Lp amplitude of affected eyes was significantly smaller than that of unaffected eyes (p < 0.001), whereas the differences in mean Dt amplitudes between affected and unaffected eyes were not statistically significant. The Lp amplitude in the affected eye was 48% or less of that in the unaffected eye in the eight patients (29%) who developed rubeosis iridis during the 9 month follow-up, and in six others. No patient whose Lp amplitude in the affected eye was greater than 48% of that in the unaffected eye, developed rubeosis. It is concluded that the Lp amplitude is abnormal in patients with acute CRVO. The degree of this abnormality bears a relation to the development of rubeosis, which might prove a useful indicator of whether to institute or withhold panretinal photocoagulation.